The Role of Hydrogen from ALD‐Al2O3 in Kesterite Cu2ZnSnS4 Solar Cells: Grain Surface Passivation. Issue 23 (31st May 2018) - Park, Jongsung; Huang, Jialiang; Yun, Jaesung; Liu, Fangyang; Ouyang, Zi; Sun, Heng; Yan, Chang; Sun, Kaiwen; Kim, Kyung; Seidel, Jan; Chen, Shiyou; Green, Martin A.; et al.
Abstract: In this research, a new route of surface passivation is reported by introducing hydrogen from the atomic layer deposited (ALD) Al2 O3 layer into pure sulfide Cu2 ZnSnS4 (CZTS) solar cells. Different amounts of hydrogen are incorporated into the Cu2 ZnSnS4 /CdS interface through controlling the thickness of the ALD‐Al2 O3 layer. The device with three cycles of ALD‐Al2 O3 yields the highest efficiency of 8.08% (without antireflection coating) with improved open‐circuit voltage of up to 70 mV. With closer examination on the passivation route of ALD‐Al2 O3, it is revealed by the surface chemisty study that the Al2 O3 can be etched away by ammonium hydroxide in the CdS buffer deposition process. Instead, the hydrogen is detected within a shallow depth from the CZTS surface, and makes a significant difference in the measured distribution of contact potential difference and device performance. This may be interpreted by the effect of hydrogen passivation of the CZTS surface by curing dangling bonds at the surface of CZTS grains. This work may provide a new direction of further improving the performance of kesterite solar cells. Abstract : The Cu2 ZnSnS4 /CdS interface is passivated by hydrogen from the ALD‐Al2 O3 process . The hydrogen from the atomic layer deposited (ALD)‐Al2 O3 process is found incorporated into the Cu2 ZnSnS4 /CdS interface. The hydrogen passivation on the CZTS grain interiors and grain surface is found to be the main reason for open‐circuit voltage enhancement and overall efficiency improvement.